The Influence of Service Quality and Tourist Satisfaction on Tourist Loyalty Visiting Garuda Wisnu Kencana Cultural Park Bali - Noviani, Ni Komang Nia; Mahadewi, Ni Made Eka; Mertha, I Wayan; Liestiandre, Hanugerah Kristiono (PT FORMOSA CENDEKIA GLOBAL, 2024)
The level of service quality provided is the main determinant in meeting tourist expectations and highlighting the excellence of a destination. (Tjiptono, 2002). This study aims to determine the effect of service quality and tourist satisfaction on the loyalty of tourists visiting the Garuda Wisnu Kencana Bali Cultural Park. This study used a sampling method, namely purposive Accidental Sampling, with a total of 150 respondents (Hair et al, 2014). The analysis technique in the study was the Structural Equation Modeling (SEM) model with the Partial Least Square (PLS) approach, and using SmartPLS 4.0 software. The results of the study showed that the tourist satisfaction variable had a significant effect on tourist loyalty (p value Sig = 0.000). The service quality variable had a significant effect on tourist satisfaction (p value Sig = 0.000). The service quality variable had a significant effect on tourist loyalty (p value Sig = 0.000). The tourist satisfaction variable can mediate the effect of service quality on tourist loyalty (p value Sig = 0.000).